A brief review of early COVID-19 global outbreak - Ridzuan, Ahmad Fikri; Mohd Izam, Muhammad Zakwan; Ismail, Nor Azliza; Zainul Abidin, Mohammad Kamaruddin; Farinordin, Farah Ayuni; Mohd Izam, Nur Amalina (Universiti Teknologi Mara (UiTM) Cawangan Pahang, 2022)
Coronavirus diseases 2019 (COVID-19), caused by the 2019 novel coronavirus (SARS-CoV-2) was declared as pandemic on 11 March 2020 by the World Health Organization (WHO). Since then, many cases and casualties involving COVID-19 happened around the world. This review aims to describe the chronology of the COVID-19 outbreak and early cases reported across the world. This virus was believed to be an artificially chimeric virus according to various reports. Previous studies believed that the COVID-19 virus spread to people all over the world via frozen seafood. Due to immediate increased in the number of cases in parts of the world, the WHO agreed that simpler diagnostic instruments that allow for faster testing were needed to detect the illness. This disease was reported to has spread to nearly every country on every continent by the end of April 2020. The number of cases and deaths related to COVID-19 increased very fast within just a year since it was first detected and has wreaked havoc on humanity. Several countries experienced thousands of cases and hundreds of deaths daily after the outbreak. Most countries with COVID-19 cases closed their borders and imposed travel restrictions to prevent the outbreak.